Traceable PEO-poly(ester) micelles for breast cancer targeting: The effect of core structure and targeting peptide on micellar tumor accumulation. (November 2017) - Garg, Shyam M.; Paiva, Igor M.; Vakili, Mohammad R.; Soudy, Rania; Agopsowicz, Kate; Soleimani, Amir H.; Hitt, Mary; Kaur, Kamaljit; Lavasanifar, Afsaneh
Abstract: Traceable poly(ethylene oxide)-poly(ester) micelles were developed through chemical conjugation of a near-infrared (NIR) dye to the poly(ester) end by click chemistry. This strategy was tried for micelles with poly(ε-caprolactone) (PCL) or poly(α-benzyl carboxylate-ε-caprolactone) (PBCL) cores. The surface of both micelles was also modified with the breast cancer targeting peptide, P18-4. The results showed the positive contribution of PBCL over PCL core on micellar thermodynamic and kinetic stability as well as accumulation in primary orthotopic MDA-MB-231 tumors within 4–96 h following intravenous administration in mice. This was in contrast to in vitro studies where better uptake of PEO-PCL versus PEO-PBCL micelles by MDA-MB-231 cells was observed. The presence of P18-4 enhanced the in vitro cell uptake and homing of both polymeric micelles in breast tumors, but only at early time points. In conclusion, the use of developed NIR labeling technique provided means for following the fate of PEO-poly(ester) based nano-carriers in live animals. Our results showed micellar stabilization through the use of PBCL over PCL cores, to have a more significant effect in enhancing the level and duration of nano-carrier accumulation in primary breast tumors than the modification of polymeric micellar surface with breast tumor targeting peptide, P18-4. Graphical abstract: